2023
DOI: 10.3389/fendo.2022.971354
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of transcriptome and microRNAome associations with gestational diabetes mellitus

Abstract: PurposeGestational diabetes (GDM) is associated with increased risk for preterm birth and related complications for both the pregnant person and newborn. Changes in gene expression have the potential to characterize complex interactions between genetic and behavioral/environmental risk factors for GDM. Our goal was to summarize the state of the science about changes in gene expression and GDM.DesignThe systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 80 publications
(287 reference statements)
0
13
0
Order By: Relevance
“…Lewis et al. performed a systematic review on maternal miRNAs in GDM however reported difficulty forming conclusions due to significant heterogeneity between studies (timepoints collected, diagnostic criteria used, inconsistent recording of ethnicity) and lack of adjustment for confounders ( 114 ). The most validated circulating miRNAs in maternal blood for GDM identified are summarized in the table below ( Table 2 ).…”
Section: Subsectionsmentioning
confidence: 99%
“…Lewis et al. performed a systematic review on maternal miRNAs in GDM however reported difficulty forming conclusions due to significant heterogeneity between studies (timepoints collected, diagnostic criteria used, inconsistent recording of ethnicity) and lack of adjustment for confounders ( 114 ). The most validated circulating miRNAs in maternal blood for GDM identified are summarized in the table below ( Table 2 ).…”
Section: Subsectionsmentioning
confidence: 99%
“…Research in both human and mouse models suggests that expression of miRs in males and females may be either consistently, differentially, or oppositely expressed in speci c diseases (i.e., one sex is upregulated and the other sex is downregulated). [32,45] More work is needed to understand sex-biased expression of the miRs in patients with T2D, and to differentiate the effects of biological sex from self-reported gender related to miR expression and risk for T2D.…”
Section: T2d [38]mentioning
confidence: 99%
“…However, the authors underlined limitations linked to the heterogeneity of the studies. A literature review of 16 studies involving 1355 patients (n = 674 with GDM, n = 681 controls), Lewis et al showed that 135 miRNAs were associated with GDM, including 8 described in at least two studies (miRNA-16-5p, miRNA -17-5p, miRNA-20a-5p, miRNA-29a-3p, miRNA-195-5p, miRNA-222-3p, miRNA-210-3p, and miRNA-342-3p) [88]. These results suggest that miRNA levels vary depending on the term of pregnancy when GDM develops, fetal sex, and BMI both before and during pregnancy.…”
Section: Expression Of Mirnas In Biofluids and Gdmmentioning
confidence: 99%